DIFFERENTIATED APPROACH TO THE TREATMENT OF INFLAMMATORY DISEASES OF THE PERIODONTIUM AND MUCOSA IN INDIVIDUALS WITH CHRONIC VIRAL DISEASES - Аbdukholikov Samandar Khamidulloevich; Islamova Nilufar Bustanovna (Bright Mind Publishing, 2025)
Viral hepatitis with parenteral transmission of pathogens is one of the most serious and pressing problems of medical science and practical health care (Zmushko E.I. et al ., 2016).